2005
DOI: 10.1037/0022-006x.73.4.769
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Neuroticism, and Emotional Expressivity: Effects on Spousal Constraints Among Individuals With Cancer.

Abstract: The authors prospectively tested the hypothesis that emotional expressivity would moderate the predictive relationship between patient neuroticism and spousal constraints among 120 individuals with cancer. The authors also examined whether patient gender further moderated the hypothesized relationships. After we controlled for Time 1 constraints, results revealed a significant emotional Expressivity x Neuroticism effect on Time 2 spousal constraints. This moderator effect was qualified by a significant Gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
2
9
0
1
Order By: Relevance
“…We found the relationship between restrictive emotionality and positive forgiveness was stronger among men with a disposition to respond in socially desirable ways. This finding is consistent with studies documenting positive links between forgiveness and social desirability (Quartana et al, 2005). Given the somewhat lower reliability of this scale, these results should be interpreted with caution.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found the relationship between restrictive emotionality and positive forgiveness was stronger among men with a disposition to respond in socially desirable ways. This finding is consistent with studies documenting positive links between forgiveness and social desirability (Quartana et al, 2005). Given the somewhat lower reliability of this scale, these results should be interpreted with caution.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with existing findings (see Ashton et al, 1998;Maltby et al, 2001;Quartana et al, 2005) neuroticism was negatively related to all three indices of forgiveness. If we accept McCullough and Hoyt's (2002) assertion that neuroticism makes individuals more vulnerable to negative emotions, then our findings suggest that this heightened vulnerability may hinder forgiveness in two ways: first, by blocking the capacity to relinquish negative affect, and second by impeding efforts to embrace positive affect.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, a study by van Middendorp et al (2005) reported that men with rheumatoid arthritis are much less willing than women to address emotions. In other research, Quartana, Schmaus, and Zakowski (2005) reported that men with cancer expressed fewer emotions than did women with cancer.…”
Section: Emotional Control and Adjustment To Prostate Cancermentioning
confidence: 99%
“…Les bénéfices sur des variables physiques demeurent toutefois non systématiques, notamment pour ce qui concerne la diminution des troubles du sommeil (non retrouvée en 2008 par De Moor et al [13] lors d'une seconde étude avec le même instrument), le mieux-être physique [64] [1,59,72]. Il n'y a que lorsque la valence des émotions exprimées est distinguée (positives vs négatives) que les auteurs repèrent une association entre disposition à exprimer des émotions négatives et diminution de la détresse émotion-nelle associée aux pensées intrusives [58].…”
Section: Résultatsunclassified